Model Konseptual Customer Order Decoupling Point pada Agroindustri Udang - Lely Herlina; M. Machfud; Elisa Anggraeni; S. Sukardi (Jurnal Ilmiah Teknik Industri, 2018)
Shrimp agro-industry is one of the food processing industries, which converts raw shrimp into high-value shrimp processed products. The production system used in shrimp agroindustry to respond market demand is a hybrid make to stock (MTS) and make to order (MTO). The decision to determine which products will be stored as supply sources and which products are made to fulfill orders is a critical decision that must be made on the MTS-MTO hybrid system. The concept of customer order decoupling point (CODP) is used to identify material flow points that connect a product with different consumers. This study aims to present a conceptual model in the MTS-MTO hibrid system based on customer order decoupling point (CODP) which is adjusted to product characteristics, production characteristics and market characteristics in the shrimp agroindustry. The results of the study are presented in a business process model template that describes the order of decisions for storing products or making products to fulfill orders and conceptual models in the form of diagrams named the CODP conceptual model on shrimp agroindustry.